Porcine Deltacoronavirus Accessory Protein NS7a Antagonizes IFN-β Production by Competing With TRAF3 and IRF3 for Binding to IKKε - Fang, Puxian; Fang, Liurong; Xia, Sijin; Ren, Jie; Zhang, Jiansong; Bai, Dongcheng; Zhou, Yanrong; Peng, Guiqing; Zhao, Shuhong; Xiao, Shaobo (Frontiers in Cellular and Infection Microbiology, 2020)
As an emerging swine enteropathogenic coronavirus, porcine deltacoronavirus (PDCoV) not only causes serious diarrhea in suckling piglets, but also possesses the potential for cross-species transmission, which has sparked growing interest in studying this emerging virus. We previously identified a novel accessory protein NS7a encoded by PDCoV; however, the function of NS7a was not resolved. In this study, we demonstrated that PDCoV NS7a is an interferon antagonist. Overexpression of NS7a notably inhibited Sendai virus (SeV)-induced interferon-β (IFN-β) production and the activation of IRF3 rather than NF-κB. NS7a also inhibited IFN-β promoter activity induced by RIG-I, MDA5, MAVS, TBK1 and IKKε, which are key components of the RIG-I-like receptor (RLR) signaling pathway, but not IRF3, the transcription factor downstream of TBK1/IKKε. Surprisingly, NS7a specifically interacts with IKKε, but not with the closely related TBK1. Furthermore, NS7a interacts simultaneously with the kinase domain (KD) and the scaffold dimerization domain (SDD) of IKKε, competing with TRAF3 and IRF3 for binding to IKKε, leading to the reduction of RLR-mediated IFN-β production. The interactions of TRAF3-IKKε and IKKε-IRF3 are also attenuated in PDCoV-infected cells. Taken together, our results demonstrate that PDCoV NS7a inhibits IFN-β production by disrupting the association of IKKε with both TRAF3 and IRF3, revealing a new mechanism utilized by a PDCoV accessory protein to evade the host antiviral innate immune response.